Cross-sectional Kelvin probe force microscopy on III–V epitaxial multilayer stacks: challenges and perspectives - da Lisca, Mattia; Alvarez, José; Connolly, James P.; Vaissiere, Nicolas; Mekhazni, Karim; Decobert, Jean; Kleider, Jean-Paul (Beilstein Journal of Nanotechnology, 2023)
Multilayer III–V-based solar cells are complex devices consisting of many layers and interfaces. The study and the comprehension of the mechanisms that take place at the interfaces is crucial for efficiency improvement. In this work, we apply frequency-modulated Kelvin probe force microscopy under ambient conditions to investigate the capability of this technique for the analysis of an InP/GaInAs(P) multilayer stack. KPFM reveals a strong dependence on the local doping concentration, allowing for the detection of the surface potential of layers with a resolution as low as 20 nm. The analysis of the surface potential allowed for the identification of space charge regions and, thus, the presence of several junctions along the stack. Furthermore, a contrast enhancement in the surface potential image was observed when KPFM was performed under illumination, which is analysed in terms of the reduction of surface band bending induced by surface defects by photogenerated carrier distributions. The analysis of the KPFM data was assisted by means of theoretical modelling simulating the energy bands profile and KPFM measurements.
Keywords: FM-KPFM; frequency-modulated Kelvin probe force microscopy; III–V multilayer stack; Kelvin probe modelling; KP modelling; SPV; surface photovoltage